Pengaruh permainan softball menggunakan model pembelajaran TGT terdahap kemampuan gerak umum - Ginanjar, Ridhan; Mamun, Syaeful; Irawan, Astri Ayu (Universitas Hamzanwadi, 2023)
The aim of this research is to determine the effect of playing softball using the team games tournament learning model on the general movement abilities of male students. The method in this research uses an experimental method and a quantitative approach with a sample size of 35 male students selected using a purposive sampling technique. The test instrument uses the barrow motor ability test. Data analysis techniques use normality, homogeneity and hypothesis tests. The research results were obtained through a simple linear regression test of the influence of softball games using the team games tournament learning model on male students' general movement abilities with a calculated t value of 4.894 and a significance value of .000. Based on the results of a simple regression test, there is an influence of playing softball using the team games tournament learning model on male students' general movement abilities. The conclusion is that there is an influence of playing softball using the team games tournament learning model on male students' general movement abilities.